Design and Development of Mobile-Based Learning Media as Teaching Materials in Grade VIII Phythagoric Theorem Material st SMP Negeri 1 Gondangrejo - Putri, Della Arinta; Trisiana, Anita; Daryono (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2023)
The purpose of this study is to find out whether the Make A Match type The aims of this research are: 1) To find out andassess the level of feasibility of designing mobile-based interactive learning media as a learning medium for Mathematics; 2) Tofind out the response or student learning outcomes in the use of mobile-based interactive learning media as eye learning mediaMathematics class VIII at SMP Negeri 1 Gondangrejo. Researchers used the Research and Development (R&D) methodwith the ADDIE development model . Collecting data using interviews, observation, and questionnaires. Testing learningmedia based on construct 2 with the Blackbox testing method Testing and validation by experts converted using a LikertScale. The results of this study can be concluded that: 1) Construct-based learning media obtains appropriate criteria accordingto media experts who have an eligibility level of 84% according to material expert validation has an eligibility level of 100%with eligibility criteria and eligibility with feasible criteria mobile-based interactive learning media as learning media forMathematics class VIII at SMP Negeri 1 Gondangrejo, namely showing that 93% of students went well and students wereable to understand and know material from the Pythagorean theorem.